2019
DOI: 10.3390/w11061303
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice and Recommendations for Modelling Global Change Impacts on Water Resource in the Himalayas

Abstract: Global change is expected to have a strong impact in the Himalayan region. The climatic and orographic conditions result in unique modelling challenges and requirements. This paper critically appraises recent hydrological modelling applications in Himalayan river basins, focusing on their utility to analyse the impacts of future climate and socio-economic changes on water resource availability in the region. Results show that the latter are only represented by land use change. Distributed, process-based hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 172 publications
(623 reference statements)
0
13
0
Order By: Relevance
“…The uncertainty in climate change projections cascades into spatio-temporal uncertainty in impacts (Koutroulis et al 2018;Salmoral et al 2019;Visser-Quinn et al 2019), posing major adaptation challenges for catchment management to improve or maintain the delivery of fES in the future. Process-based modelling approaches are generally preferred to assess climate change impacts and define decision-making strategies for adaptation in relation to fES (Runting et al 2017;Momblanch et al 2019a). Most modelling studies that assess adaptation interventions in the landscape (Bangash et al 2013;Dunford et al 2015;Fan et al 2016;Liu et al 2017;Mandle et al 2017;Huang et al 2019;Underwood et al 2019) with the intention to offset negative climate change impacts overlook river fES and their links to landscape services.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty in climate change projections cascades into spatio-temporal uncertainty in impacts (Koutroulis et al 2018;Salmoral et al 2019;Visser-Quinn et al 2019), posing major adaptation challenges for catchment management to improve or maintain the delivery of fES in the future. Process-based modelling approaches are generally preferred to assess climate change impacts and define decision-making strategies for adaptation in relation to fES (Runting et al 2017;Momblanch et al 2019a). Most modelling studies that assess adaptation interventions in the landscape (Bangash et al 2013;Dunford et al 2015;Fan et al 2016;Liu et al 2017;Mandle et al 2017;Huang et al 2019;Underwood et al 2019) with the intention to offset negative climate change impacts overlook river fES and their links to landscape services.…”
Section: Introductionmentioning
confidence: 99%
“…The economic activities of individuals affect the ecology, environment, and natural resources, and are in turn affected by them [2]. Many studies are indicating the existence of increasing demand and pressure on ecology, environment, and natural resources in terms of quantity and quality based on many factors but mostly due to population growth rate, urbanization, industrialization, expanding agricultural irrigation, and climate change, all of which affect the socioeconomic structure of societies [3][4][5][6][7][8]. These pressures, which are mainly caused by human activities, generally occur on soil and water resources [2,9] and creates difficulties for food supply [10] where sources are main factors, at least, for food security.…”
Section: Introductionmentioning
confidence: 99%
“…& Attempts to co-opt the hydrologic literature to game water sharing (Wine 2019b) or limit government responsibility for degradation of treasured aquatic ecosystems (Wine 2019d). & Limited data access (Klein 1998;Avni et al 2015;Momblanch et al 2019) to scientists who stray from sanctioned discourse (Wine 2019d).…”
Section: Hydrology Securitizedmentioning
confidence: 99%
“…Scholars at Risk also documents certain incidents of insults against academic freedom.) The role of members of the international community whose freedom of expression is protectedin desecuritizing hydrologic scienceis also advanced by Momblanch et al (2019): "transboundary research projects should be promoted by independent international institutions" that are not influenced by securitizing state actors. However, through case by case review of studies emerging from the securitized domain, valid and sound scientific studies may be found that can serve as a basis for equitable water sharing in the transboundary context.…”
Section: Toward a Physical Hydrology Basis For Equitable Water Sharingmentioning
confidence: 99%